COMMENTS ON THE ARTICLE BY ZH.P. SHARNOVA, YE.YE. TIKHOMIROVA, A.N. TSYGINA, V.G. PINELIS «ANGIOTENSIN CONVERTING ENZIME GENE I/D POLYMORPHISM AND PROMISSING OF RENOPROTECTIVE AND IMMUNOSUPRESSIVE THERAPY IN CHILDREN WITH NEPHROTIC SYNDROME» - A.Yu. Asanov (Union of pediatricians of Russia, 2007)
.